Assessment of Prognostic Factors of Acute Hepatitis Among Pediatric Patients: A Cross‐Sectional Study - Neda Ezoddin; Fateme Ziamanesh; Alireza Ramandi; Pejman Rohani; MohammadHassan Sohouli; Hosein Alimadadi (JGH Open, 2025)
ABSTRACT Introduction Early identification of acute hepatitis etiology and specific management is crucial for reducing morbidity and mortality. Therefore, this study aims to investigate the prognostic factors of acute hepatitis in children. Methods This cross‐sectional study was conducted on children with diagnosis of acute hepatitis According to the criteria of ESPHAGAN, admitted to the Children's Hospital from March 2018 to March 2023. Data were analyzed using SPSS statistical software. Results A total of 164 patients with acute hepatitis were included, comprising 78 patients with acute liver failure and 86 patients without acute liver failure. Viral infections were identified as the most common etiology of acute hepatitis and were significantly more prevalent in patients without acute liver failure. Wilson's disease was significantly more prevalent in patients with acute liver failure. All patients with viral etiology recovered. Among the 24 patients with Wilson's disease, 14 (58.3%) underwent transplantation, 4 (16.6%) were deceased, and 6 (25%) survived without transplantation. Patients with other etiologies did not experience any mortality, with only 13.8% undergoing transplantation due to autoimmune causes. Low albumin (< 2.5), prolonged PT (> 22), elevated INR (> 3), encephalopathy, low phosphorus (< 3), and a duration of more than 7 days between symptom onset and hospitalization significantly increased the risk of mortality or need for transplantation in patients with acute liver disease. Conclusion Albumin levels, PT, INR, encephalopathy, phosphorus levels, and the duration between symptom onset and hospitalization are significant prognostic factors for acute hepatitis in pediatric patients.